To the moon! : the true story of the American heroes on the Apollo 8 spaceship - Kluger, Jeffrey; Shamir, Ruby (Puffin Books, 2019)
Presents the story of the Apollo Eight mission to the moon less than two years after the tragic loss of the Apollo One crew in a fire inside the craft. In a hurried race against Russia to be the first nation to travel to the moon, NASA enlisted the brave crew composed of Frank Borman, Jim Lovell, and Bill Anders to make history.